2020
DOI: 10.1097/01.numa.0000721828.72471.4a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the peer, manager, and system influence on patient safety

Abstract: he aim to achieve zero preventable harm in healthcare systems remains an important but elusive goal. 1 Recent reports suggest that medical error is the third leading cause of death in the US. 2 As healthcare organizations have increased their focus on implementing tactics to improve patient safety, there remains doubt about their effectiveness. 3 One intervention that has shown promise for decreasing errors in health systems is the assessment of organizational perceptions of patient safety culture and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…This supports researchers who found that manager expectations, feedback, and communication about events are important factors in promoting a safe patient culture 11-13. This finding informed a deeper investigation of the level of contribution peers and managers have in creating a nonpunitive response to error 14…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This supports researchers who found that manager expectations, feedback, and communication about events are important factors in promoting a safe patient culture 11-13. This finding informed a deeper investigation of the level of contribution peers and managers have in creating a nonpunitive response to error 14…”
Section: Discussionsupporting
confidence: 79%
“…[11][12][13] This finding informed a deeper investigation of the level of contribution peers and managers have in creating a nonpunitive response to error. 14…”
Section: Punitive Responsementioning
confidence: 99%
“…PSC should consider whether nurses receive information on AEs that have occurred in their unit and the measures adopted to prevent the detected risks [43][44][45][46][47]. Likewise, another factor to be taken into account is the availability of information related to what is considered a reportable situation and to good practices.…”
Section: Discussionmentioning
confidence: 99%